Antecedents and consequences of the evoked K-Complex. - Bastien, Celyne. (University of Ottawa (Canada), 1993)
Three experiments were run in order to determine the antecedents and consequences of the evoked K-Complex. In all three experiments, a train of auditory stimuli was presented during stages 2, 3 and 4 of sleep. In experiment 1, the intensity of the stimulus (80 and 60 dB SPL), its rise-and-fall time (2 and 20 ms) and its tonal frequency (500, 1000 and 2000 Hz) were manipulated. The evoked K-Complex consisted of two different negative components peaking at approximately 350 ("N350") and 550 ("N550") ms, respectively, and followed by a positive component peaking at approximately 900 ("P900") ms. K-Complexes occurred more often with high intensity, fast rise-and-fall time stimuli. When a K-Complex was evoked, the amplitude and latency of the different components remained invariant regardless of the intensity, rise-and-fall or tonal frequency of the stimulus. The K-Complex therefore appears to be an all-or-none phenomenon. On trials on which a K-Complex could not be on elicited, N350 was still visible although much attenuated. On these trials, its amplitude was further reduced when stimulus intensity was lowered. N350 might need to reach a certain critical threshold before the much larger N550-P900 complex is elicited. Experiment 2 examined the effects of rate of presentation on the evoked K-Complex. In different conditions, brief duration tone pips were presented every 5, 10 or 30 sec. K-Complexes were elicited most often when the rate of stimulus presentation was slowest (i.e., every 30 sec) compared to when it was faster (i.e., every 5 or 10 sec). When a K-Complex was evoked, the amplitudes of N350 and N550 were greater with the 30 than the 10 or 5 sec rate of stimulus presentation. A micro-analysis was carried out when 3 consecutive K-Complexes were elicited. With the faster rates of presentation, N350 and N550 following the second and third occurrence of the K-Complex were significantly attenuated compared to the first occurrence. There was no difference in N350 and N550 amplitudes among the 3 consecutive occurrences during the Slow condition. The decay in amplitude over consecutive occurrences of the K-Complex was interpreted as due to either habituation or refractory processes. Experiment 3 was designed to determine the function of the K-Complex. It has been considered to reflect either an arousal or a sleep protector mechanism. A spectral analysis of the EEG prior to and following the presentation of a stimulus was compared on trials on which a K-Complex was and was not elicited. Tone pips were presented every 20 sec during non-REM sleep. FFTs were computed on the EEG prior to and following stimulus onset. In the absence of a K-Complex, a small but significant power elevation following stimulus onset was apparent during Slow Wave Sleep. There were no changes in EEG activity when a K-Complex was elicited. The K-Complex therefore appears to prevent arousal that might otherwise occur to external stimuli.
Keywords: Psychology, Physiological.